(untitled) (Research, Society and Development, 2020)
This study has the purpose to analyze the implementation and historical route of the Colégio São Sebastião do Rio de Janeiro, located in the Guanabara’s Bay region. Thereunto, we adopt the bibliographic and documentary methodology; we analyzed articles, Jesuit letters and the texts written by Serafim Leite (1890–1969). The research is justified by the need to understand how the teaching organization occurred of teaching took place in the beginnings of Brazilian education. In this way, we can reflect about the past, the present and the future from the perspective of rupture and continuity. With the results obtained, we can see that the intense conflicts, in Guanabara’s Bay, meant the development of Rio de Janeiro and the establishment of the school institution. Through discussions, we can reflect about the area of history and historiography of education. This permeates historical investigations about educational phenomena, college’s structures and the contents taught by Jesuit priests to seminarians who, in the future, would fulfill the function of transmitting the Catholic faith and teaching indigenous children. The literacy and religious teachings, that happened in the bê-á-bá’s houses, for native children, they were essential to develop the habit of reading the Bible and convert the Gentile to the Christian. We consider that the colonization of Rio de Janeiro was only possible due to two factors: Portuguese Crown and Catholic Church. While the Portuguese administration intended to expand his territories and to get benefits whit the products offered by the new localities found, the actions of the Jesuit priests were to expand Christianity that had suffered repression by Protestantism.